Analysis of the 1/2 Subharmonic-primary Parametric Resonance of Viscoelasticity Driving Belt System - Li Gaofeng (Jixie chuandong)
Based on the viscoelasticity driving belt of transverse vibration equations under the action of parametric excitation,by using the method of multiple scales,the approximate solution of the 1 /2 subharmonic- primary parametric resonance equations is obtained. The influence of the viscoelasticity parameter,detuning parameter and an axial moving speed on the amplitudes of steady- state response boundaries is analyzed. Some new dynamical phenomena are revealed of viscoelasticity driving belt.